Application of the updated International IgA Nephropathy Prediction Tool in children one- or two-years post-biopsy. - Sean J. Barbour; Rosanna Coppo; Lee Er; María Luisa Russo; Zhihong Liu; Jie Ding; Xuhui Zhong; Ritsuko Katafuchi; Norishige Yoshikawa; Hong Xu; Shoji Kagami; Yukio Yuzawa; et al. (2024)
The pediatric International IgA Nephropathy (IgAN) Prediction Tool comprises two models with and without ethnicity and is the first method to predict the risk of a 30% decline in estimated glomerular filtration rate (eGFR) or kidney failure in children at the time of biopsy using clinical risk factors and Oxford MEST histology scores. However, it is unknown if the Prediction Tool can be applied after a period of observation post-biopsy. Using an international multi-ethnic cohort of 947 children with IgAN, 38% of whom were followed into adulthood, the Prediction Tool was updated for use one-year after biopsy. Compared to the original pediatric Prediction Tool, the updated post-biopsy Prediction Tool had a better model fit with higher R2D (51%/50% vs 20%), significant increase in 4-year C-statistics (0.83 vs 0.73/0.69, ΔC 0.09 [95% confidence interval 0.07-0.10] and ΔC 0.14 [0.12-0.15]) and better 4-year calibration with lower integrated calibration indices (0.74/0.54 vs 2.45/1.01). Results were similar after internal validation and when the models were applied two-years after biopsy. Trajectories of eGFR after a baseline one-year post-biopsy were non-linear and those at higher predicted risk started with a lower eGFR and experienced a more rapid decline over time. In children, eGFR had a variable rate of increase until 15-18 years old then decreased linearly with a more rapid decline in higher risk groups that was similar to young adults of comparable risk. Thus, the original pediatric Prediction Tool should be used in children at the time of biopsy, and the updated pediatric Prediction Tool should be used to revaluate risk one- or two-years after biopsy.